Electrical and thermal optimization of energy-conversion systems based on thermoelectric generators. (1st February 2022) - Pennelli, Giovanni; Dimaggio, Elisabetta; Macucci, Massimo
Abstract: Thermoelectric generator devices, which convert heat directly into electrical power, have a great potential for energy scavenging and green energy harvesting applications. The exploitation of such a potential requires a proper design of both the electrical circuit that drives the electrical load and the thermal part, in particular when the thermoelectric generator is coupled with the hot and cold heat sources through thermal resistances. We propose a straightforward approach to take into account both thermal and electrical issues, by means of an equivalent electric circuit model that can be solved with widely available simulator programs, such as SPICE. Our approach is shown to be effective for supporting the design and optimization of thermoelectric systems from the point of view of the output power and of the efficiency. In particular, with our model we are able to point out that thermal resistance matching optimizes the thermal fluxes only in first approximation: for a particular case study we find that the optimal module thermal resistance is 20% larger than the contact resistance. We also show that the electrical matching for the maximum output power must be carefully considered for each particular thermoelectric module and load condition. Highlights: Circuital model for thermoelectric conversion systems. Design and optimization of a thermoelectric conversion system. Quantitative comparison between different power management strategies. Thermal matching conditions with non-ideal heat exchange. Design of the number of pn elements for a thermoelectric module.